Analysis Of Career Development And Compensation Of Employee Performance With Promotion As A Variable Intervening At PT Hki Toll Road Construction Pekanbaru – Padang, Siring Padang Section - Tomy Herlambang; Kiki Farida Ferine; Mesra B. (Yayasan Multidimensi Kreatif, 2023)
This study aims to determine and analyze the effect of career development and compensation on employee performance with promotion as an intervening variable. The location of the research was conducted at PT HKI Pembangunan Toll Road Pekanbaru - Padang, Padang Sicincin. The number of respondents was 82 respondents who were contract employees. The research method is Structural Equation Model (SEM) Analysis with SmartPLS version 4 calculations. The results of direct influence show that there is a positive but not significant influence between development on employee performance. There is a positive but not significant influence between career development and promotion. There is a positive and significant influence between compensation and employee performance. There is a positive and significant influence between compensation and promotion. There is a positive but not significant influence between promotion and employee performance. While the results of indirect influence show that there is a positive but not significant influence between career development on employee performance through promotion. There was a positive but not significant effect between compensation on employee performance through promotion